INTEGRATION OF VALUES AND PRACTICES OF CHARACTER EDUCATION: A COMPARATIVE ANALYSIS BETWEEN IBN MISKAWAIH AND THOMAS LICKONA - Siti Khodijah; Hermi Cahyawati; Maragustam; Muhammad; Sibawaihi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This research adopts a comparative analysis method to explore the integration of values and character education practices, based on the philosophical-spiritual perspective of Ibn Miskawaih and the psychological-social perspective of Thomas Lickona. The focus is on the internalization of moral values in character education, highlighting the role of family and society. Through literature research, this article reveals how character education can be a solution to the contemporary moral crisis. The research results show the importance of a holistic approach in character education, which integrates intellectual and moral aspects to form intelligent individuals with integrity. This research contributes to the understanding of effective character education in facing today's social challenges.